Real‐time confocal laser endomicroscopic evaluation of primary liver cancer based on human liver autofluorescence. Issue 2 (4th November 2016) - Maki, Harufumi; Kawaguchi, Yoshikuni; Arita, Junichi; Akamatsu, Nobuhisa; Kaneko, Junichi; Sakamoto, Yoshihiro; Hasegawa, Kiyoshi; Harihara, Yasushi; Kokudo, Norihiro
Abstract : Background: Confocal laser endomicroscopy (CLE) is available for real‐time microscopic examination. This study aims to evaluate the usefulness of intraoperative CLE examination as a modality to evaluate surgical margins in surgery for primary liver cancer. Methods: A probe‐based CLE system (Cellvizio 100, Mauna Kea Technologies, Paris, France) was used. The subjects comprised seven specimens obtained from six patients with primary liver cancer in November 2015. The probe was manually attached to the surfaces of specimens, and images were collected without external fluorophores. CLE images were compared with hematoxylin and eosin‐stained slides. Fluorescence intensity (FI) values of the CLE images were assessed using luminance‐analyzing software. Results: CLE examination visualized non‐cancerous regions in the background liver as regular structures with high fluorescence because of human liver autofluorescence. Conversely, hepatocellular carcinoma and intrahepatic cholangiocarcinoma were depicted as irregular structures with low fluorescence. The median FI values of the non‐cancerous regions and the cancerous regions were 104 (79.8–156) and 74.9 (60.6–106), respectively, and were significantly different ( P  = 0.031). Conclusions: The probe‐based CLE enables real‐time differentiation of cancerous regions from non‐cancerous tissues in surgical specimens because of human liver autofluorescence. CLE can be used to confirm negative surgical margins in the operating room. J. Surg. Oncol. 2017;115:151–157 . © 2016 Wiley Periodicals, Inc.